Get a free home demo of LearnNext

Available for CBSE, ICSE and State Board syllabus.
Call our LearnNext Expert on 1800 419 1234 (tollfree)
OR submit details below for a call back


Mathematical Induction

Have a doubt? Clear it now.
live_help Have a doubt, Ask our Expert Ask Now
format_list_bulleted Take this Lesson Test Start Test

Mathematical Induction - Lesson Summary

A statement that has a definite truth value that is, true or false, is called a mathematical statement.

Deductive reasoning involves logical steps to arrive upon a particular case from a general case. Inductive reasoning is the counter-part of deductive reasoning.

This is commonly used in mathematics, where collecting and analysing data is the norm.

This is a process of establishing general principles from particular cases.

In mathematics, we come across many mathematical statements, formulae and theorems that cannot be proved directly.

The principle used to prove mathematical statements, formulae and results involving positive integers, is called the principle of mathematical induction.

To prove mathematical statements through the induction method, certain principles have to be followed. The basic principle behind mathematical induction is that if a statement is true, then the statement that follows the first statement is also true, and so on.

Let P(n) be a statement, where n is a natural number, such that:

The statement is true for n = 1 or P(n) is true.

If the statement is true for n = k, where k is a positive integer, then the statement is also true for n = k + 1.

P(k) is true ⇒ P(k + 1) is true. This is also referred as the inductive step.

Assuming the statement is true for n = k in the inductive step is called inductive hypothesis.

Then, P(n) is true for all natural numbers n.

Principle one is a statement of fact, while principle two is a condition.

If P(n) is true for all n ≥ 2, then step 1 starts from n = 2 and we verify the result of P(2).

If the second principle is true for n = k, then it is also true for n = k + 1.


1 + 3 + 5 + ........ + (2n-1) = n2

P(n): 1 + 3 + 5 + ........... + (2n-1) = n2

n = 1,2,3,....

P(1):1 = 12

Thus, P(1) is true.

This statement can be considered as a fact.

Now, take n equal to two.

P(2):1 + 3 = 4 = 22

Thus, P(2) is true.

Next, consider n = 3.

P(3): 1 + 3 + 5

= 9 = 32

Thus, P(3) is true.

Consider P(k) is true.

Need to prove P(k + 1) is true.

1 + 3 + 5 +.........+(2k - 1) ------- (1)

1 + 3 + 5 +.........+ (2k - 1) + [(2k + 1) - 1] = k2 + [(2k + 1) - 1]

= k2 + 2k + 1

=(k + 1)2

=P(k + 1)

∴ P(k + 1) is true.

Hence, P(n) is true for all natural numbers n.


Feel the LearnNext Experience on App

Download app, watch sample animated video lessons and get a free trial.

Desktop Download Now
Try LearnNext at home

Get a free home demo. Book an appointment now!